Il granduca Cosimo I de' Medici e il programma politico dinastico nel complesso di San Lorenzo a Firenze - Bietti, Monica; Ferretti, Emanuela (Ricerche. Architettura, Pianificazione, Paesaggio, Design, 2021)
This volume collects interdisciplinary contributions that explain the complexity of Cosimo I patronage among the Laurentian complex. Thus it gives original and key interpretations on episodes central to the historiographical debate regarding some of the most important figures of the late Renaissance such as Michelangelo, Pontormo, Vasari and Vincenzo Borghini. San Lorenzo Basilica in Florence represented for Cosimo I a chance of continuity with the Medici Family, the place where to perpetuate the dynastic policy of his ancestors. The volume offers an updated picture on some relevant issues that will run through the second half of the XVI century that will eventually be developed by the Medici's Grand Dukes in the next two centuries.